Using forecasts to uncover the loss function of FOMC members - Christian Pierdzioch; Jan-Christoph Rülke; Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
We revisit the sources of the bias in Federal Reserve forecasts and assess whether a precautionary motive can explain the forecast bias. In contrast to the existing literature, we use forecasts submitted by individual FOMC members to uncover members' implicit loss function. Our key finding is that the loss function of FOMC members is asymmetric: FOMC members incur a higher loss when they underpredict (overpredict) in ation and unemployment (real GDP) as compared to an overprediction (underprediction) of similar size. Our findings add to the recent controversy on the relative quality of FOMC forecasts compared to staff forecasts. Together with Capistrán's (2008) finding of similar asymmetries in Federal Reserve staff forecasts our results suggest that differences in predictive ability do not stem from differences in preferences. This is underlined by our second result: forecasts remain biased even after accepting an asymmetric loss function.
Keywords: E58; E37; E27; 330; Federal Open Market Committee; forecasting; asymmetric loss function; monetary policy